The parents role in independent character development of elementary school children during the covid-19 pandemic - Kurniawan, Machful Indra (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
This article aims to provide knowledge about parents role in developing the independent character of elementary school children during the Covid-19 pandemic. The method used in this study was a qualitative research method using literature studies. Literature studies are carried out by searching for literature that is appropriate with research from various written sources, both print and non-print, such as books, scientific papers contained in national and international journals and seminar proceedings. The parent's role in independent character cultivation of elementary school students during the COVID-19 pandemic is a must, considering the current state of learning at home so that parents become the spearhead in the education process, one of which is in terms of developing the independent character of elementary school children. Independent character is necessary to be developed in elementary school children during the current COVID-19 pandemic, due to this pandemic, people including elementary school children, must be able to carry out protocols independently, such as maintaining hand hygiene, avoiding touching their eyes, nose and mouth, applying coughing or sneezing ethics, wearing a mask, keeping a safe distance. Therefore, for elementary school children to be able to carry out these protocols independently, the parents' role in developing the independent character of elementary school children during the current Covid-19 pandemic is considered important. The importance of developing independent character is because at the age of elementary school children are still not used to maintaining personal hygiene, especially personal hygiene when outside home.